Analysis of plasmonics-based MSM photodetector with optimized parameters - Masouleh, Farzaneh; Mashayekhi, Hamid; Das, Narottam (Not known, 2013)
Finite difference time-domain (FDTD) method is used to simulate the light absorption in a novel plasmonic-based photodetector with nano-gratings. Slit width is one of the effective parameters for the light absorption enhancement in metal-semioconductor-metal photodetectors. FDTD simulation results show ~ 13.5-times light absorption enhancement according to the changes in duty cycle and number of nano-gratings on each side of the slit.